The response of plasma interleukin-6 and its soluble receptors to exercise in the cold in humans - Patterson, S.; Reid, S.; Gray, S.; Nimmo, M. (Journal of Sports Sciences, 2008)
In this study, we wished to determine whether the changes in metabolism observed during exercise in the cold are associated with changes in interleukin-6 (IL-6) and/or its soluble receptors. Eight healthy male participants performed 1 h of cycling exercise at 70% VO2max in a control (20°C) and cold (0°C) environment. Plasma concentrations of IL-6, soluble IL-6 receptor (sIL-6R), and sgp130 were measured before exercise, at 30 and 60 min of exercise, and 60 min after exercise. Substrate oxidation was estimated through measures of pulmonary gas exchange recorded between 50 and 55 min of cycling. Exercise in the cold resulted in an increase (P < 0.05) in carbohydrate oxidation (mean 2.58 g · min-1, s = 0.49 at 20°C vs. 2.85 g · min-1, s = 0.58 at 0°C) and a decrease (P < 0.05) in fat oxidation (0.55 g · min-1, s = 0.17 at 20°C vs. 0.38 g · min-1, s = 0.16 at 0°C) compared with the control trial. Interleukin-6 concentrations were elevated (P < 0.05) after 60 min of exercise in both the cold and control trials, with no differences between trials at any instant. Neither sIL-6R nor sgp130 was affected by exercise or the environment. The alterations in carbohydrate and fat utilization during 1 h of exercise in the cold are not paralleled by changes in plasma concentrations of IL-6 or its soluble receptors.